2022
DOI: 10.1111/febs.16577
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of skeletal muscle repair and regeneration in health and disease

Abstract: Skeletal muscle is a structurally and functionally remarkable tissue composed of multinucleated post-mitotic muscle fibres. These fibres are filled with an exquisite, near crystalline array of assembled contractile proteins, capable of coupling ATP utilization to mechanical muscle contraction. Fully differentiated muscle has an incredible ability to protect and repair itself from significant muscle injuries. In fact, through activation of a resident population of stem cells known as satellite cells, muscle fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…Satellite cells in skeletal muscle may play a crucial role in maintaining skeletal muscle homeostasis and repair, while they can also be damaged by inflammation and oxidative stress [ 63 ]. A study by Komaru et al demonstrated that a low-B6 diet led to a decrease in satellite cell pool in mouse skeletal muscle compared to a diet with an adequate level of B6 [ 64 ].…”
Section: Potential Mechanisms Underlying the Association Of Low B6 St...mentioning
confidence: 99%
See 1 more Smart Citation
“…Satellite cells in skeletal muscle may play a crucial role in maintaining skeletal muscle homeostasis and repair, while they can also be damaged by inflammation and oxidative stress [ 63 ]. A study by Komaru et al demonstrated that a low-B6 diet led to a decrease in satellite cell pool in mouse skeletal muscle compared to a diet with an adequate level of B6 [ 64 ].…”
Section: Potential Mechanisms Underlying the Association Of Low B6 St...mentioning
confidence: 99%
“…A study by Palin et al suggested that carnosine has protective effects against oxidative damage in porcine myoblast cells [ 66 ]. This protection is believed to be mediated through the p38 MAPK intracellular signaling pathway, which is essential for cellular response to oxidative stress [ 63 ]. A subsequent study by Lie et al has suggested that carnosine may promote muscle growth in pigs by stimulating the proliferation of satellite cells through the Akt/mTOR/S6K signaling pathway [ 67 ].…”
Section: Potential Mechanisms Underlying the Association Of Low B6 St...mentioning
confidence: 99%
“…Por último, se encuentran descritas diferentes alteraciones asociadas a cáncer en los mecanismos de reparación muscular. El músculo-esquelético es un tejido que posee una notable capacidad para reemplazar las fibras musculares dañadas o destruidas, 32 que depende en gran medida de las contribuciones de las células satélite, 33 quiescente ancladas a la membrana plasmática de las miofibras maduras 34 y precisan señales de su entorno que les indiquen el momento de salir de tal estado de quiescencia para iniciar la diferenciación de las células satélite vírgenes hacia mioblastos comprometidos y, eventualmente, a miofibras multinucleadas. 35 Alrededor de ellas se encuentra el nicho de las células madre, cuyos componentes estructurales forman parte de una matriz extracelular (MEC) expansiva, que contiene las señales bioquímicas necesarias para la activación de la miogénesis y las etapas subsiguientes de regeneración.…”
Section: Fisiopatología De La Sarcopenia En El Cáncerunclassified
“…As skeletal muscles exhibit powerful plasticity to adapt to various stimuli, skeletal muscle regeneration is facilitated by mononucleated precursor stem cells termed satellite cells (Baghdadi & Tajbakhsh, 2018; Ceafalan et al, 2014). Upon muscle injury, satellite cells are rapidly activated, proliferated, and fused to form new myofibers and/or repair the damaged fibers (Fukada et al, 2022; Michele, 2022). However, detailed regeneration mechanisms in the skeletal muscle are poorly understood.…”
Section: Introductionmentioning
confidence: 99%